China Systematic Country Diagnostic : Towards a More Inclusive and Sustainable Development - World Bank Group (World Bank, Washington, DC, 2018)
The 19th National Congress of the Communist Party of China (CPC) reaffirmed the country’s commitment to eliminating poverty and promoting shared prosperity and inclusive growth. In this regard, the China systematic country diagnostic (SCD) is supportive of the priorities of the Party Congress. China’s historic rapid growth resulted in a poverty decline unprecedented in its speed and scale. Rapid growth was made possible by a wide range of reforms, which transformed a state-dominated, planned, rural, and closed economy to a more market-based, urbanized, and open economy. China is on its way to eliminating extreme poverty, but the population vulnerable to poverty will remain relatively large. China is expected to continue to make strong progress toward eliminating extreme poverty despite the slowdown of economic growth. The World Bank projects extreme poverty, based on the international public private partnership (PPP) United States (U.S.) 1.90 dollars per day poverty line, to decline to 0.5 percent by 2018. According to this higher poverty line, China is projected to have a poverty rate of 3.9 percent or 54.6 million people below this higher poverty line by 2018.